A bacterial enzyme may correct 2-HG accumulation in human cancers - Yin, William J. (Frontiers in Oncology, 2023)
A significant proportion of lower-grade glioma as well as many other types of human cancers are associated with neomorphic mutations in IDH1/2 genes (mIDH1/2). These mutations lead to an aberrant accumulation of 2-hydroxyglutarate (2-HG). Interestingly, even cancers without mIDH1/2 can exhibit increased levels of 2-HG due to factors like hypoxia and extracellular acidity. Mounting evidence demonstrates that 2-HG competitively inhibits α-ketoglutarate dependent enzymes, such as JmjC-domain-containing histone demethylases (JHDMs), ten-eleven translocation enzymes (TETs), and various dioxygenases (e.g., RNA m6A demethylases and prolyl hydroxylases). Consequently, the hypermethylation of DNA, RNA, and histones, and the abnormal activities of hypoxia-inducible factors (HIFs) have profound impacts on the establishment of cancer metabolism and microenvironment, which promote tumor progression. This connection between the oncometabolite 2-HG and glioma holds crucial implications for treatments targeting this disease. Here, I hypothesize that an ectopic introduction of a bacterial 2-hydroxyglutarate synthase (2-HG synthase) enzyme into cancer cells with 2-HG accumulation could serve as a promising enzyme therapy for glioma and other types of cancers. While absent in human metabolism, 2-HG synthase in bacterial species catalyzes the conversion of 2-HG into propionyl-CoA and glyoxylate, two metabolites that potentially possess anti-tumor effects. For a broad spectrum of human cancers with 2-HG accumulation, 2-HG synthase-based enzyme therapy holds the potential to not only correct 2-HG induced cancer metabolism but also transform an oncometabolite into metabolic challenges within cancer cells.